Analisis Self Control Penggunaan Gadget pada Perilaku Prokrastinasi : (Studi Kasus Mahasiswa Ilmu Komunikasi UIN Sumatera Utara) - Kartika, Yunda; Azhar, Anang Anas (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
Students really need the ability to control themselves in minimizing the occurrence of procrastination due to the use of gadgets. To avoid things that interfere with individual productivity, students must have high self-control. The higher the self-control, the lower the procrastination that occurs. The function of this research is to find out about how self-control students should exercise to minimize procrastination behavior due to uncontrolled use of gadgets. This procrastination can result in certain situations and emotions that are not desired, such as anger, guilt, worry, and so on, and can hamper a person's productivity, and often results in stress and pressure due to unfinished work. In combination these impacts can disrupt a person's happiness, well-being and success in various aspects of life. This is why self-control is very important and students really need self-control. This self-control refers to an individual's ability to regulate their own thoughts, feelings and actions. In this case, data analysis is used in a qualitative descriptive method using a phenomenological approach. with documentation, interviews and observation techniques. This research uses an analysis of self-regulation theory, which is one of the main components of human personality. Self-regulation refers to an individual's capacity to manage their own behavior and involves processes of observation, self-evaluation and response. The object of this research is solving cases regarding self-control in the use of procrastination behavior gadgets by UIN North Sumatra students. The instruments/tools used in qualitative research are interview guides, observation lists, and documentation instructions. Some findings from existing research are that there is a substantial connection between excessive gadget use and self-control to prevent students from delaying assignments, while other findings procrastination and self-regulation are significantly negatively correlated. This shows that some students need higher self-control so that there is low procrastination.